等量代换
根据算式在( )里填上合适的数。
□+□+□=21
□=( 7 )
○+○+○+○+○=30
○=( 6 )
☆+☆+☆+☆+☆+☆+☆=42
☆=( 6 )
1
等量代换
□+□+△=56
△+△+□+□=72
□=( 20 )
△=( 16 )
△ + 56 =72
△=72-56
=16
□+□+16=56
□+□=56-16
□+□=40
□=20
2
○+△=10
○+○+○+△+△ =26
○=( 6 )
△=( 4 )
○+20=26
○=26-20=6
6 +△ =10
△=10-6=4
3
○+○+○=21
○+○+□=18
○-□=( 3 )
○-□=21-18=3
4
□+□+☆=13
□+□+ □ +☆+☆=21
□=( 5 )
☆=( 3 )
□+13+☆ =21
□+☆=21-13=8
□+☆=8
□+□+☆=13
□+ 8 =13
□=13-8
=5
5
△+☆+△+△=27 □+△=13
☆+☆=△+△+△ □- △=3
△=( ) □=( )
☆=( ) △=( )
△+△=○+○+○
△=( )
○=( )
6
41-○-□=5
□=○+○+○
○=( 9 )
□=( 27 )
41-○- (○+○+○) =5
41-(○+ ○+ ○+ ○)=5
○+ ○+ ○+ ○=41-5=36
4X ○=36
○=9
7
□+□+□=15
△+△+△=12
□+△=( )
□+□=△+△+△ ⊙=△△△△
△+△=○+○+○+○ △=○○○
□+□+△=( )个○ ⊙-△=( )个○
8
○×□=30
□×△=40
○×3=18
○=( )
□=( )
△=( )
9
等量代换 来自淘豆网m.daumloan.com转载请标明出处.